STRUKTUR KOMUNITAS MAKROZOOBENTHOS DI KAWASAN MANGROVE DESA BAGAN DELI KECAMATANMEDAN BELAWAN (Structure of Macrozoobenthos Community on Mangrove in Bagan Deli Village, Medan Belawan district) - Tri Wulandari; Hesti Wahyuningsih; Ahmad Mutadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Activitieson mangrove areas Bagan Deli Village, Medan Belawan district resulted inwater quality decrease, causing changes in ecological condition of the biota, especiallymacrozoobenthos. This research aims to determine the community structure of macrozoobenthosand water quality based on Abundance and Comparison (ABC) curve. This research was conductedin the mangrove area of the village of Bagan Deli Medan District Belawan from March until April2016. It was done by using purposive random sampling method on three stations. The samplingmacrozoobenthos and watter quality measurement was done and a half month. There were 13species of macrozoobenthoswhich found, namely Telescopium telescopium, Turritella terebra,Nassarius reeveanus, Cerithide acingulata, Chicoreus capucinus, Nerita lineata, Cerithidea obtusa,Littoraria melanostoma, Cassidula aurisfelis, Natica Tigrina, Uca vocans and Uca rosea. Thehighest density is worth 900 ind/dm2. Diversity index was ranged from 1,79 to 2,09 which is in highrated level. Uniformity index was ranged from 0,7 to 0,82 and dominance index was ranged from0,15 to 0,2. The conditional of mangrove area in Bagan Deli village is in the medium pollutedcategory based on the ABC curve.Keywords : ABC curve, Community Structure, Macrozoobenthos, Pollution Levels